Higher-order correlation functions of nonuniform Ising chain - Sorokov, S.I. (Condensed Matter Physics, 2002)
We suggest algorithms for calculating arbitrary order correlation functions (S₁i. . . Sinin)c and distribution functions (Si₁. . . Sinin) of a nonuniform Ising chain.